Motivated explanation - Patterson, Richard; Operskalski, Joachim T.; Barbey, Aron K. (Frontiers in Human Neuroscience, 2015)
Although motivation is a well-established field of study in its own right, and has been fruitfully studied in connection with attribution theory and belief formation under the heading of “motivated thinking”, its powerful and pervasive influence on explanatory processes is less well explored. Where one has a strong motivation to understand some event correctly, one is thereby motivated to adhere as best one can to normative or “epistemic” criteria for correct or accurate explanation, even if one does not consciously formulate or apply such criteria. By contrast, many of our motivations to explain introduce bias into the processes involved in generating, evaluating, or giving of explanations. Non-epistemic explanatory motivations, or (following Kunda’s usage), “directional” motivations, include self-justification, resolution of cognitive dissonance, deliberate deception, teaching, and many more. Some of these motivations lead to the relaxation or violation of epistemic norms, combined with an effort to preserve the appearance of accuracy; others enhance epistemic motivation, so that one engages in more careful and thorough generational and evaluative processes. In short, “real life” explanatory processes are often constrained by multiple goals, epistemic and directional, where these goals may mutually reinforce one another or may conflict, and where our explanations emerge as a matter of weighing and satisfying those goals. Our proposals are largely programmatic, although we do review a good deal of relevant behavioral and neurological evidence. Specifically, we recognize five generative processes, some of which cover further sub-processes, and six evaluative processes. All of these are potential points of entry for the influence of motivation. We then suggest in some detail how specific sorts of explanatory motivation interact with specific explanatory processes.